DESIGN AND DEVELOPMENT OF DOODLE ART BOOK ABOUT 2020 USING THE RESEARCH AND DEVELOPMENT METHOD - Lindy Rubianti; Tony Wibowo (Universitas Internasional Batam, 2022)
2020 is one of the most eventful years of 21st century. Unprecedented events like covid-19, Australian bushfire, C/2020 F3 and NEOWISE Comet. This study aims to record events that happened on 2020 in doodle art format. Doodle art is an abstract art that is free to express and can convey messages through a digital work. We utilize R&D methodology in developing the doodle art book by researching publication, articles, news and happening to define trending topics about the year 2020. For development, we used MDLC model method to develop the doodle art into illustration book. The results of the study prove that doodle is a branch that deserves further research and investigation, such as its effectiveness as a medium for delivering messages compared to other media, and how certain demographic groups respond to messages conveyed by doodles.